Resilience of the teacher in the learning in rural schools in Peru - Segovia-Quesada, Silvia (2020)
The purpose of the research is to analyze the essence of the teacher’s experience in teaching and learning situations in rural schools of Peru. Attention to diversity of cultures, social contexts, students that are served in educational institutions becomes difficult and complicated, it implies having a resilient teacher, with characteristics such as self-esteem, autonomy, creativity, and confidence, able to adapt to any circumstance. The research was developed with the parameters of qualitative research, specifically the hermeneutical phenomenology in education, for having a reflexive character-emerging from the educational task, where the empirical world is interpreted and understood, looking for the meaning of the lived experiences of the teachers in their pedagogical work in which it is intended to unveil the essence of them. The interview was used as a technique and the anecdote as an instrument, in which five teachers participated: three boys and two women, with the following axes of analysis: expectation, frustration, sadness, happiness and satisfaction. The information was processed through the understanding of the experience in order to elaborate meanings of the same fact. The study concludes that resilience occurs when the teacher adapts to various unfavorable situations presented at school, making use of personal characteristics that allow him to turn limitations into strengths and thus overcome adversity.